Improving the practice of financial support of industrial development - Shemiakina, N.V.; Gorinenko, A.S. (Економіка промисловості, 2014)
The article analyzes the financial and credit support of industrial development. The paper analyses the current state of investment activity in Ukraine and the development issues in the investments of industry. It analyzes problems connected with forming the investment policy and a number of measures aimed at improving the situation. In the context of the global financial crisis as well as political instability and economic deficiencies of Ukrainian governance, the investment climate in Ukraine in 2008-2009 was significantly degenerated. The article analyzes the structure of capital investment, and showsthe dynamics of gross capital investment in industry, and the GDP. It’s proposed possible ways of using and improving methods of optimizing the structure of financial sources of investment in the main headband. The article analyzes the current state of innovation activities in the Ukrainian industry in recent years. The article analyzes the trends and structure of the investment in the innovation products and processes. The paper reviews a variety of financial resources of technical development on industrial enterprises. As well as article analyzes the financial results of Ukrainian companies and revealed their negative trend. The article analyzes the net profit of industrial enterprises. The paper is determined that banks should be the main financial centers of industrial development in the modern condition. It’s determined that alternative funding mechanisms of the technical development in the industry has not been sufficiently developed. The paper is considered the international experience of financial support of industrial development. It’s determined that an achievement of economic stability and renewal of industrial production requires an active investment policy and justified long-term strategic direction. It should be aimed at the creation, capacity and efficiency of scientific and technical potential of industry according to national requirements. The research of financing industrial development issues allowed outlining the potential directions for improvement of the system of financing industrial development in the medium term.